Essential Bipolar Fuzzy Ideals in Semigroups - Thiti Gaketem; Pannawit Khamrot (International Journal of Analysis and Applications, 2023)
In this paper, we give the concepts of essential bipolar fuzzy ideals in semigroups. We discuss the basic properties and relationships between essential bipolar fuzzy ideals and essential ideals in semigroups Finally, we extend to 0-essential bipolar fuzzy ideals in semigroups.